1990
DOI: 10.1577/1548-8659(1990)119<0431:bgdona>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Genetic Detection of Natural and Artificial Hybridization of Chinook and Coho Salmon in Northern California

Abstract: Allelic products of seven isozyme loci were used to identify presumptive hybridization between chinook salmon Oncorhynchus tshawytscha and coho salmon O. kisutch in northern California. First‐generation hybrid salmon (N = 3) were observed in samples from a tributary creek to the Trinity River; from rearing ponds at Camp Creek, a tributary to the Klamath River (N = 14); and from the ocean salmon fishery near Eureka (N = 2). The sample from the Camp Creek rearing ponds consisted of progeny from an inadvertent cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…The unintended introgression of hatchery stock within other resident populations has occurred as the result of other Pacific salmon translocations (Bartley, Gall, & Bentley, 1990;Hess et al, 2011;Spies et al, 2007;Utter, 2000). In some instances, when this introgression was between populations with divergent life histories, outbreeding depression has been demonstrated (Gharrett, Smoker, Reisenbichler, & Taylor, 1999;Gilk et al, 2004).…”
Section: Kokanee-sockeye Hybridization In Skaha Lakementioning
confidence: 99%
“…The unintended introgression of hatchery stock within other resident populations has occurred as the result of other Pacific salmon translocations (Bartley, Gall, & Bentley, 1990;Hess et al, 2011;Spies et al, 2007;Utter, 2000). In some instances, when this introgression was between populations with divergent life histories, outbreeding depression has been demonstrated (Gharrett, Smoker, Reisenbichler, & Taylor, 1999;Gilk et al, 2004).…”
Section: Kokanee-sockeye Hybridization In Skaha Lakementioning
confidence: 99%
“…Thus in both cases further study would appear likely to reveal that they are of common occurrence. In contrast, the single occurrence of chinook (Oncorhynchus rshuyytscha) and coho (0. kisutch) salmon hybridization detected in a California river (Bartley et al, 1990) would seem a rare event. In spite of the extensive electrophoretic surveys of Pacific salmonid populations, no other natural hybrids have been detected biochemically between these species.…”
Section: Hybridizationmentioning
confidence: 99%
“…Natural hybridization between Chinook ( Oncorhynchus tshawytscha ) and Coho salmon ( Oncorhynchus kisutch ) has been documented but is rare (Bartley et al, 1990; Chevassus, 1979; Johnson & Ringler, 1981). Its infrequency has been attributed to prezygotic isolation mechanisms that prevent viable development (Bartley et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Natural hybridization between Chinook ( Oncorhynchus tshawytscha ) and Coho salmon ( Oncorhynchus kisutch ) has been documented but is rare (Bartley et al, 1990; Chevassus, 1979; Johnson & Ringler, 1981). Its infrequency has been attributed to prezygotic isolation mechanisms that prevent viable development (Bartley et al, 1990). Utter et al (1989) found no evidence of Chinook–Coho salmon hybrids in a Chinook salmon population structure study of 86 collection sites from the Babine River in British Columbia to the Sacramento River in California.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation